Comparison of Chemistry Questions in Access To Higher Education Exams in France, Switzerland and Turkey - Ergun, M. (My University, 2013)
The purpose of this study was to compare the chemistry questions asked in access to higher education exams in France, Switzerland, and Turkey. For this purpose, chemistry questions asked in the baccalaureate exam in France, matriculation exam in Switzerland, and undergraduate admission examination in Turkey were examined. A qualitative research method of content analysis, horizontal and descriptive research method was used in this study. The results show that access to higher education exams in these countries differ according to each country's educational system. There are also similarities and differences among these countries in chemistry questions asked in access to higher education exams. Suggestions have been made to improve access to higher education exams in Turkey.
Fransa, İsviçre Ve Türkiye'de Yükseköğretime Geçiş Sınavlarındaki Kimya Sorularının Karşılaştırılması
Keywords: Baccalaureate; Chemistry; France; Higher Education Exams; Matura; Switzerland; Turkey